Pengaruh Kompres Air Hangat Rebusan Jahe Terhadap Nyeri Punggung Pada Ibu Hamil Trimester III - Laetare, Tresy Patricia; ., Meldawati; Hidayah, Nurul; Mariana, Frani (POLTEKKES KEMENKES MANADO, 2024)
Background: According to WHO, the incidence of low back pain or back pain is still high at 15-45%, with back pain in pregnancy having a varying incidence of approximately 50% in England and Scandinavia to close to 70% in Australia. During pregnancy, mothers definitely experience discomfort, especially in the third trimester, such as back pain. To reduce the use of pharmacological treatment, herbal plants can be used for non-pharmacological treatment, one of which is warm water compress of ginger decoction, which can help reduce complaints of back pain. Warm water compresses of ginger decoction have been proven to help reduce back pain in third-trimester pregnant women. Ginger is an herbal plant that contains essential oils that can reduce back pain. Objective: To determine the effect of warm water compresses of ginger decoction on back pain in third-trimester pregnant women in the Pekauman Banjarmasin Health Center Working Area. Methods: The study employed the Pre-Experiment Design method, which included a One-Group Pretest-Posttest design. The sampling method used a quota-sampling technique. The number of samples was 20 respondents with complaints of back pain in the third trimester. Data analysis using the Wilcoxon Signed Rank Test.. Results: The results obtained before being given a ginger compress were that some respondents had severe pain levels: 11 respondents (55.0%), while 9 respondents had moderate pain levels (45.0%), and after being given a ginger compress, mild pain levels were 16 respondents (80%), while moderate pain levels were 4 respondents (20%). Wilcoxon Signed Rank Test results obtained p-value = 0.000 (<0.05). Conclusion: There is an effect of warm water compresses of ginger decoction on back pain in third-trimester pregnant women in the Pekauman Banjarmasin Health Center Working Area.